Asset Inequality Does Matter: Lessons from Latin America - Nancy Birdsall; Juan Luis Londo\~no (Inter-American Development Bank, Office of the Chief Economist, 1997)
In light of recent results, the fight against poverty in Latin America has been far from satisfactory. The standard approach of multicultural credit agencies will continue to be limited if it does not stress the central role of the distribution as well as the accumulation of productive assets, especially human capital. After removing fiscal and trade distortions with structural reforms, insufficient levels of human and physical capital accumulation and highly skewed asset distribution are critical growth constraints for Latin America. Policies aimed at reducing inequalities in assets accumulation should be at the center of a new approach for poverty eradication and increased growth in Latin America at the start of the new century.
Keywords: 330